Effect Of Silica Fume Inclusion On Properties Of High Strength Concrete Containing High Volume Of Steel Slag - Mohsin, Mohammad Nazeem (Universiti Sains Malaysia, 2018)
The use ground granulated blast furnace slag in concrete is advantageous from economic, environmental and technical points of view. However, the use of slag especially in high volume may negatively affect the strength and other properties of concrete. Therefore, this study explores the feasibility of using silica fume as partial replacement of slag in high strength concrete containing high volume of slag. A control high strength concrete mix was proportioned to have a 28 days strength of 70 MPa. A similar mix was proportioned but 60% of the ordinary Portland cement was replaced with slag on mass-for-mass basis. Further, another four concrete mixes were proportioned by partially replacing the slag content with silica fume at 5, 10, 15 and 20%. The effects of the incorporation of silica fume on workability, density, compressive strength, porosity and water absorption of the concrete were investigated. The results exhibit that the use of slag in combination with silica fume tends to reduce the workability of the high strength concrete. Concrete mixes containing slag as well as combination of slag and silica fume exhibit higher density than the control concrete. The inclusion of silica fume improves the strength of the high strength concrete containing high volume of slag, in particular at higher silica fume content, but the strength obtained does not exceed that of the control concrete mix. The influence of silica fume inclusion on porosity and water absorption of the high strength concrete containing high volume of slag is to significantly reduce both porosity and water absorption in particular at higher silica fume content and longer curing period. The results show that concrete containing 20% silica fume registers a slump value of 13 mm, with density of 2544 kg/m3, compressive strength of 76.03 MPa, porosity of 5.29% and water absorption of 3.23% at the age of 56 days.